Deterministic and Probabilistic Analyses of the Bearing Capacity of Screw Cast in Situ Displacement Piles in Silty Soils as Measured by CPT and SDT - Lehar Leetsaar; Leena Korkiala Tanttu (The Baltic Journal of Road and Bridge Engineering)
The bearing capacity of screw cast in situ displacement piles is mostly unexplored. There is also insufficient research on piles in silty soils. Therefore, five cone penetration tests (CPT) and one piezocone penetration test (CPTu) using direct methods were utilised to determine the load-bearing capacity of four displacement piles in Estonia. In addition to the CPT sounding data, static-dynamic test (SDT) results were used to analyse the load-beating capacity of the piles. Both deterministic and probabilistic methods were used in the analysis. Characteristic values as a 95% reliable mean and 5% fractile values for sounding parameters, according to the Eurocode 7, were included. Additionally, Monte Carlo simulation was included in the reliability-based design (RBD). The bearing capacities of screw cast in situ displacement piles in silty soils, here based on the CPT and SDT sounding data, were similar. The adaptation of SDT results for the CPT direct methods for pile load-bearing capacity analysis certainly deserves attention and further investigation. For both sounding types, the Eurocode 7 method provided the best results for all piles. The results of pile-bearing capacities in the absolute difference varied within ±11% between the average, RBD and characteristic values.